Evaluation of shear strength properties of unbound PET plastic in blends with demolition wastes. (30th November 2020) - Perera, Sahan; Arulrajah, Arul; Wong, Yat; Maghool, Farshid; Horpibulsuk, Suksun
Abstract: Polyethylene terephthalate (PET) plastic is one of the most abundant types of plastics that contributes to the municipal solid waste stream. Construction and demolition (C&D) waste materials account for 60% of the waste disposal by weight in Australia and a significant percentage of this waste also ends up in landfills. This research study evaluated the key geotechnical parameters of two types of C&D materials, namely recycled concrete aggregate (RCA) and crushed brick (CB) in blends with 5% shredded PET flakes (by mass). The blends were subjected to direct shear test (DST) and consolidated drained (CD) triaxial tests, in order to evaluate the shear strength properties. Both DST and CD triaxial test results indicated that adding 5%PET can improve the friction angles and apparent cohesion values of the control RCA and CB materials. Based on the shear strength characteristics, it was ascertained that 5%PET + 95%C&D blends have the potential to be used in pavement base/subbase applications, substituting the virgin quarry aggregates.